Cannabis and cannabinoids in dermatology: a systematic review and meta-analysis of quantitative outcomes - Sermsaksasithorn, Pim; Nopsopon, Tanawin; Samuthpongtorn, Chatpol; Chotirosniramit, Korn; Pongpirul, Krit (Frontiers in Pharmacology, 2025)
ObjectiveCannabinoids, present in Cannabis sativa, modulate the signaling and receptor expression of the endocannabinoid system (ECS), potentially impacting various skin conditions. However, current evaluations of their clinical effectiveness remain largely descriptive. This study aimed to quantitatively assess the effectiveness of cannabinoids, including Cannabis sativa extracts, in treating dermatologic disorders.DesignSystematic review and meta-analysis.Data sourcesPubMed, Embase, Scopus, Web of Science, and CENTRAL from inception to 30 June 2024.Eligibility criteria for selecting studiesWe included randomized controlled trials and observational studies that evaluated the efficacy or effectiveness of medical cannabis or cannabinoid-based interventions in managing dermatologic conditions, regardless of the comparator type.Data extraction and synthesisTwo reviewers independently extracted data and assessed risk of bias. Outcomes were categorized into subjective outcomes, objective outcomes, and disease-specific composite scores. Meta-analyses used standard mean differences (SMDs) with 95% confidence intervals (CIs). Study quality was assessed using RoB 2 and ROBINS-I tools.ResultsWe included 3,359 participants from eleven randomized controlled trials, three quasi-experimental studies, and three observational studies. Interventions included topical formulations of cannabis extract ointment, cannabidiol, N-acylethanolamine (PEA), alkylamides, and HU-210. A statistically significant reduction in pruritus was observed among participants treated with cannabinoids (SMD = −0.29, 95% CI: −0.52 to −0.06, I2 = 0%). No significant effects were found for skin dryness (SMD = −0.22, 95% CI: −0.58 to 0.14, I2 = 20%), erythema (SMD = −0.33, 95% CI: −0.65 to 0.00, I2 = 0%), or quality of life (SMD = −0.15, 95% CI: −0.64 to 0.34, I2 = 58%). Disease-specific scores for atopic dermatitis (SMD = −0.19, 95% CI: −0.44 to 0.05, I2 = 0%) and transepidermal water loss (SMD = 0.16, 95% CI: −0.60 to 0.93, I2 = 68%) also showed no significant differences.ConclusionCannabinoids produced a modest but statistically significant reduction in pruritus, suggesting clinical relevance for symptom management. However, no significant benefits were observed for other dermatologic outcomes. Larger, standardized randomized trials are needed to clarify their therapeutic potential in dermatology.Systematic Review Registrationidentifier CRD42023397189.